The grant writing and crowdfunding guide for young investigators in science - Lebrun, Jean-Luc; Lebrun, Justin (World Scientific, 2017)
"The Grant Writing and Crowdfunding Guide for Young Investigators in Science is a guide that prepares young investigators in Science to step up to the challenge of funding their own research. Writing a successful grant demands much more than a first-class inquisitive scientific mind, as young investigators soon discover. The book presents the best strategies they should adopt to prepare themselves prior to taking the grant plunge. It then helps them draft a reasonable budget plan, assemble a winning grant team, write a stellar preproposal, and reassure the funding agencies that the financial risk they take in investing in them will produce great returns. The book also helps them write a grant title, abstract, and a specific aims section that highlight the significance, impact, and innovativeness of their project. It presents specific tools to catch problems early and avoid rejection. To improve the submission, the book presents a new source of funding: crowdfunding. It gives the young investigator a way to collect preliminary results and involve the public in their work. New investigators are usually lost when attempting to write their first grant application. The book is dedicated to them. It acts as a coach that supplements the work of the mentor. It is meant to be concrete. Although it considers the review practices of two of the largest grant organizations in the world, NIH and NSF, it is sufficiently generic to apply to other science funding agencies."--Publisher's website
Title from World Scientific website
Keywords: Science / Research grants; Research grants; Proposal writing for grants; Electronic books; Forschungsfinanzierung; Crowdfunding